Digital Transformation of Public Asset Management via Web-Based Lifecycle System for Diskominfo Kota Bandung - Jasman Pardede; Noval Rizky Nugraha; Muhammad Zaki Mahran Mufid; Muhammad Mulyawan (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2026)
Public asset management at Diskominfo Kota Bandung faces challenges related to manual administrative procedures, including data inconsistencies and difficulties in asset tracking. This community service activity aimed to introduce a prototype of the "Kelola Baraya" web-based asset lifecycle management system as a digital transformation initiative to support transparency and accountability in regional property management. The activity was conducted through field observations, stakeholder interviews, system development, and prototype demonstration sessions involving representatives from Diskominfo Kota Bandung. The developed prototype integrates QR Code-based asset identification, centralized monitoring dashboards, geotagging features, and multi-role validation workflows. Evaluation through demonstration and feedback sessions indicated that the proposed features were considered relevant to organizational needs and have the potential to support more structured and efficient asset management processes. The activity successfully introduced the concept of digital asset management and laid the foundation for future system implementation within the institution.